The Impact of Critical Rationalism Expanding the Popperian Legacy through the Works of Ian C. Jarvie - Sassower, Raphael; Laor, Nathaniel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
As a student and disciple of Karl Popper and longtime managing editor of Philosophy of the Social Sciences, Ian C. Jarvie extended the notion of Critical Rationalism to be useful in anthropology, aesthetics, film studies, and various social sciences. In this Festschrift, contributors from a range of interests and disciplines engage with the Popperian legacy and Jarvie's scholarly and editorial work in Critical Rationalism to contextualize it in the contemporary and broader intellectual landscape. Ultimately, these original essays not only honor Jarvie's legacy, but expand it to cross the philosophical divide between analytic and continental schools of thought. In so doing, the authors bring the state-of-the-art achievements of Critical Rationalism to the fore. .
1. Introduction: The Legacy of Ian C. Jarvie; Nathaniel Laor and Raphael Sassower -- Part I: Philosophy of the Social Sciences -- 2. How Should Social Engineers Develop Critical Social Science?; Nimrod Bar-Ann -- 3. On Economic Methodology Literature from 1963 to Today; Lawrence Boland -- 4. The Republic of Science and Its Constitution: Some Reflections on Scientific Methods as Institutions; Jesús Zamora Bonilla -- 5. The Situational Logic of Disciplinary Scholarship; Fred D'Agostino -- 6. Academia as Cargo Cult; Steve Fuller -- 7. Our Current Sense of Anxiety; John A. Hall -- 8. How to Integrate Economic, Social and Political Theory: Revise the Rationality Principle; John Wettersten -- Part II: Critical Rationalism -- 9. The Future of Critical Rationalism; Joseph Agassi -- 10. The Dark Side of Technological Progress; Mario Bunge. - 11. Fractured Knowledge 'Fake News'; Jagdish Hattiangadi -- 12. Ian Jarvie, Critical Rationalism and Methodological Individualism; Jeremy Shearmur. - 13. Jarvie on Rationality and Cultural Relativism; Kei Yoshida. - Part III: The Popperian Legacy -- 14. Popper's Institutional Turn; Rafe Champion. - 15. The Republic of Science and its Citizens: What Role May Humanities Play Within the Popperian Framework?; José A. Colen and Scott Nelson -- 16. Karl Popper, the Open Society and the Cosmopolitan Democratic Empire; Malachi Haim Hacohen. - 17. Popper and Hume: Two Great Skeptics; Zuzana Parusniková -- 18. The Tyranny in Science: The Case Of Hugh Everett's Universal Wave Theory Formulation Of Quantum Mechanics; Sheldon Richmond -- 19. Jarvie's Rationalitätstreit; Paul A. Roth -- 20. The Political Philosophy of Science in Historical Perspective: The Road Through Popper and Polanyi to the Present; Stephen Turner -- 21. Popper's Conception of Scientific Discovery and its Relation to the Community of Science; H. T. Wilson -- Part IV: Film Studies / Aesthetics -- 22. Some Thoughts on Artists' Statements; Jeanette Bicknell -- 23. Confusing the Scientific and Moral Appeals of Suppressing Vice; Augustine Brannigan -- 24. World Three and Cognitivism: Philosophy in Film; Byron Kaldis. - 25. Jarvie, Popper, McLuhan, and Me; Paul Levinson.
Keywords: Social sciences -- Philosophy; Science -- Philosophy; Sociology -- Methodology; Culture -- Study and teaching; Culture; Social Theory; Philosophy of Science; Sociological Methods; Cultural Studies; Sociology of Culture